Vehicle Warranty Data Information System at PT. Capella Dinamik Nusantara In Banda Aceh - Muhammad; Munawir (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This research aims to analyze the weaknesses and shortcomings of the current information system in motorcycle warranty management at PT. Capella Dinamik Nusantara, as well as design and propose a new information system that is more efficient and effective. The research methods used include observation, interviews, and document analysis. The results show that the current information system faces several obstacles, such as inadequate application systems, lack of motorcycle warranty data availability, and insufficient human resources, especially in the field of Information Technology. Therefore, this research proposes a new integrated information system for motorcycle warranty management, with features such as user creation and approval settings by administrators, motorcycle warranty document creation, and motorcycle warranty certificate processing by administrators. Additionally, this research also designs a data structure that includes admin, customer, and motorcycle warranty tables. With the implementation of this new information system, PT. Capella Dinamik Nusantara is expected to improve the efficiency and effectiveness of motorcycle warranty management and enhance the accuracy of warranty data reports.